(untitled) (New Hope, PA., 2000)
A collection of articles from various professionals, discussing the details of investing in asset-backed securities. Main topics addressed include non-real estate backed ABS, collateralized debt obligations, residential real-estate backed ABS, accounting, commercial mortgage backed securities, and analysis of ABS.
Keywords: Asset-backed financing,Securities,Tài sản - hậu thuẫn tài chính,Thị trường chứng khoán; United States,United States,Hoa Kỳ,Hoa Kỳ